Pengaruh Pola Asuh Orang Tua Terhadap Prestasi Belajar Peserta Didik Kelas IV SDI Onekore 5 Kabupaten Ende - See, Siprianus (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
The formulation of the problem in this research is: Is there an influence of parental parenting on the learning achievement of class IV students at SDI Onekore 5? The aim to be achieved is to determine the influence of parental parenting on the learning achievement of class IV SDI Onekore 5 students. The respondents in this research were 30 class IV SDI Onekore5 students. The research method used in this research is quantitative expos facto type. Data collection techniques use questionnaires and are supported by documentation. The data analysis technique uses simple linear regression analysis with the help of the SPSS version 23 program. The results of the research show that there is a positive and significant influence of parental parenting variables on the learning achievement of class IV students at SDI Onekore 5 as indicated by a coefficient of determination of 0.299, which means that parental parenting has an influence on student learning outcomes by 29.9%.